Representación política y derechos de las trabajadoras en Argentina. El caso de la Convención Constituyente de 1957 - Adriana María Valobra (Centre de Recherches sur les Mondes Américains, 2013)
This article examines the debates and developments around Article 14b of the 1957 Constitution of Argentina, on the basis of an investigation into the congressional records for the constitutional assembly and commercial and political journals, among other sources. In particular, it highlights the contributions of the women who took part in the debate, whose interpretations differed from those that had existed up to that point. In this sense, the study sheds light on the legal and political aspect of an issue that has not yet been considered in this regulatory context: female workers' rights. Together, the specific characteristics of the congressional debates and the final text of the constitutional article provide a gender-oriented perspective that aids the understanding of two further aspects: how politics constructs gender and how gender constructs politics.